Gambaran Keanekaragaman Pola Konsumsi Pangan Ibu Hamil di Wilayah Kerja Puskesmas Guntung Payung Tahun 2013 - Rusman Effendi; Saidatunnisa Saidatunnisa; Juairiah Juairiah; STIKES Husada Borneo; Puskesmas Sungai Tabuk; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
Protein Energy Malnutrition (PEM) is the cause of anemia, bleeding, abnormal maternal weight and maternal infection. Research aim to portray the diversity of food consumption of pregnant women in Work Area Public Health Center GuntungPayung in 2013. Research design used a descriptive approach to the method of survey. The population study is pregnant women in the working area health centers. Method sample use Random Sampling Systematic with 79 respondents. The results showed as many as 56 respondents consume staple foods 3-4 (70.6%) cover, staple food rice 79 respondents (100%), maize 27 respondents (34.2%), and sago Tuber 37 respondents (34 , 2%), Wheat 43 respondents (54.4%). A total of 44 respondents consume more than 4 types of food side dishes (55.6%), chicken meat (90%), eggs (64.6%), tilapia (39.2%), anchovies (45.6%) , Tofu (87,3%), soybean (87.3%). A total of 59 respondents consume more than 4 kinds of vegetables (87.4%), spinach (77.2%), cinnamon leaf (49.4%), cassava leaves (74.7%), papaya (59.5%), eggplant (44.3%). A total of 45 respondents consumed more than four types of fruit (56.9%),including: apple (31.6%), bananas (57%), papaya (63.3%), watermelon (59.5%), oranges ( 46.8%), mango (29.1%), guava (34.2%), yip (30.4%), and oil (36.7%), Food dietary restrictions in pregnant women. There are no restrictions as much as 74 respondents (93.7%), abstinence sea fish (3.9%), shrimp (2.5%).